Pemahaman mengenai surat-surat pilihan q.s. at-tiin (95), hukum bacaan waqaf dan washal, serta hadis tentang ciri-ciri orang munafik - Fadilah, Muhammad Afif (Maliki Interdisciplinary Journal, 2026)
This article comprehensively discusses the content of Surah At-Tiin, the rules of waqaf and washal in the Qur’an, as well as the hadith that explains the characteristics of hypocrites. Surah At-Tiin emphasizes the nobility of human creation in the best form and reminds mankind of the potential degradation that occurs when one deviates from faith and righteous deeds. The rules of waqaf and washal are explained as essential aspects of proper Qur’anic recitation to preserve the intended meaning of the verses. The discussed hadith describes the behavior of hypocrites—lying, breaking promises, and betraying trust—which must be avoided by Muslims to maintain moral purity and faith. The findings of this study enrich academic understanding while providing practical implications for religious education and the development of pious Muslim character. The method used in this article is a literature study, which is a research approach that relies on reviewing various sources such as scientific journals, articles, books, and relevant documents.